Non-intubated Thoracoscopic Surgery-Tips and Tricks From Anesthesiological Aspects: A Mini Review - Fabo, Csongor; Oszlanyi, Adam; Lantos, Judit; Rarosi, Ferenc; Horvath, Theodor; Barta, Zsanett; Nemeth, Tibor; Szabo, Zsolt (Frontiers in Surgery, 2022)
Background: In the last few decades, surgical techniques have been developed in thoracic surgery, and minimally invasive strategies such as multi-and uniportal video-assisted thoracic surgery (VATS) have become more favorable even for major pulmonary resections. Methods: We perfo6rmed a computerized search of the medical literature (PubMed, Google Scholar, Scopus) to identify relevant articles in non-intubated thoracoscopic surgery using the following terms [(non-intubated) OR (non-intubated) OR (awake) OR (tubeless) OR (regional anesthesia)] AND [(VATS) OR (NIVATS)], as well as their Medical Subject Headings (MeSH) terms. Five hundred and three papers were found, and those focusing on NIVATS were excluded. Papers published before 2015, letters, and editorials were also excluded. Results: Based on the outcomes of the reviewed literature and our practice, it seems that pathopsysiological concerns can be overcome by proper surgical and anesthetic management. All risks are compensated by the advantageous physiological changes that result in better patient outcomes. With the maintenance of spontaneous breathing, the incidence of potential adverse effects of mechanical ventilation, such as ventilator-induced lung injury and consequent postoperative pulmonary complications, can be reduced. The avoidance of muscle relaxants also results in the maintenance of contraction of the dependent hemidiaphragm and lower airway pressure levels, which may lead to better ventilation-perfusion matching. Conclusion: NITS-VATS seems to be a feasible and safe method in selected patients with evolving importance as a part of the minimally invasive surgical and anesthetic conception and has a role in reducing perioperative complications, which is crucial in the thoracic surgical patient population.